Role of hormone replacement therapy in relieving oral dryness symptoms in postmenopausal women: a case control study - Lina Wang; Lilei Zhu; Yao Yao; Yajuan Ren; Hongcan Zhang (BMC, 2021)
Abstract Background To evaluate the efficacy of hormone replacement therapy in relieving oral symptoms in postmenopausal women presenting with genitourinary symptoms along with oral dryness. Methods A case-control study was conducted after selecting 60 postmenopausal women. Oral dryness status of all the patients was evaluated with the help of questionnaire related to oral dryness. These subjects were divided into case group and control group on the basis of response to questionnaire of oral dryness. Unstimulated saliva samples were obtained and analyzed for estimation of salivary estradiol levels by enzyme linked immune sorbent assay technique. After analyzing the result of salivary estradiol levels, case group was subjected to hormone replacement therapy (HRT). The patients were followed up for their response towards oral dryness as well as salivary estradiol levels after the therapy. Results The mean salivary estradiol level before HRT was significantly more among control group as compared to case group (p value < 0.001). Most of the patients complained of dry mouth (26 out of 30); reduced amount of saliva in the mouth (25 out of 30); dry mouth at night (28 out of 30); dry mouth during the day (25 out of 30) before HRT. These complains were significantly reduced after the therapy. The mean salivary estradiol in the case group levels increased significantly after HRT (p value < 0.001). Conclusion The salivary estradiol levels were reduced in post menopausal women with the complain of xerostomia as compared to those without the complain of xerostomia. Further these levels can be recovered with the help of hormone replacement therapy.